Peran Teknologi Pembelajaran Dan Kegiatan Praktik Dalam Meningkatkan Kompetensi Mahasiswa Transportasi Laut Di Sekolah Vokasi Pelayaran Indonesia. - Bayan, Zifran Allamahul; Syamsiah, Sitti Syamsiah (Politeknik Pelayaran Sumatera Barat, 2025)
This study aims to evaluate the impact of educational technology and practical experience on enhancing the competencies of maritime transportation students in Indonesian maritime vocational institutions. A qualitative research method was employed, with data analysis conducted through three main stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the use of educational technologies such as e-learning platforms, simulation software, and blended learning models can strengthen students’ cognitive abilities and improve the overall effectiveness of the learning process. On the other hand, practical experiences, including sea internships and laboratory simulations, play a vital role in developing students’ operational competencies and preparing them mentally for careers in the maritime sector. The integration of educational technology and hands-on learning has been proven to significantly enhance students’ knowledge, skills, and professional ethics. This study highlights the importance of strengthening technological infrastructure, improving the quality of practical training, and providing policy support to produce globally competitive graduates.